Measuring the Carboxypeptidase and γ-Glutamyltranspeptidase Activities of Lager and Ale Yeasts to Assess Their Impact on the Release of Odorant Polyfunctional Thiols Through Fermentation - Coraline Calicis; Romain Christiaens; Natacha Loquet; Margaux Simon; Sonia Collin (Molecules, 2025)
Two enzymatic assays, based on release of p-nitroaniline and its spectrophotometric detection at 405 nm, were used to screen lager and ale brewing yeasts for carboxypeptidase and γ-glutamyltranspeptidase activity. Both activities were found in all the investigated yeasts and did not significantly distinguish Saccharomyces cerevisiae from S. pastorianus species. Large between-strain differences were measured for both carboxypeptidase (from 1.61 A/h for BRAS-45 to 41.71 A/h for E-30) and γ-glutamyltranspeptidase (from 1.26 A/h for US-05 to 48.72 A/h for S-33). No correlation was found between either enzymatic activity and the previously published ability of Saccharomyces yeasts to degrade glutathionyl or γ-GluCys- precursors to free polyfunctional thiols. Only for fermentation at lower temperatures does carboxypeptidase activity seem relevant for identifying the most interesting candidates. Measuring transport efficiency and β-lyase activities individually on the three possible intermediates emerges here as more promising for future flavor potential screening.